1978
DOI: 10.1073/pnas.75.3.1546
|View full text |Cite
|
Sign up to set email alerts
|

Morphine sulfate stimulates the adenylate cyclase in mouse caudate nuclei.

Abstract: The effect of several concentrations of morphine on the activity of adenylate cyclase [ATP pyrophosphate-lyase (cyclizing); EC 4.6.1.1] was measured in homogenates of caudate nuclei of mice. Morphine stimulated the enzyme at 500 MM and inhibited slightly at 5 MM. Morphine stimulation was blocked by naloxone. Depending on its dose, morphine also increased or decreased the stimulating effect of dopamine on the dopamine-sensitive adenylate cyclase activity of caudate homogenate. Like dopamine, morphine's effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
1984
1984

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The absolute dependence on GTP for enkephalin activity suggested that the presence of guanine nucleotide in the tissue slices but not in homogenate was the cause for the divergent results. The reported stimulation of the adenylate cyclase by heroic concentration of morphine (Pun et al, 1975;Dismukes and Daly, 1975;Tang and Cotzias, 1978) could be due to the nonspecific ionic effect of the cationic drug molecule similar to that of the monovalent cations. The apparent sitmulation of striatal adenylate cyclase by 10 pwdextrorphan could be an example of cationic drug stimulation of striatal adenylate cyclase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute dependence on GTP for enkephalin activity suggested that the presence of guanine nucleotide in the tissue slices but not in homogenate was the cause for the divergent results. The reported stimulation of the adenylate cyclase by heroic concentration of morphine (Pun et al, 1975;Dismukes and Daly, 1975;Tang and Cotzias, 1978) could be due to the nonspecific ionic effect of the cationic drug molecule similar to that of the monovalent cations. The apparent sitmulation of striatal adenylate cyclase by 10 pwdextrorphan could be an example of cationic drug stimulation of striatal adenylate cyclase.…”
Section: Discussionmentioning
confidence: 99%
“…However, opiate inhibition of the brain adenylate cyclase has been equivocal. There are reports in the literature demonstrating that (a) opiate inhibited the adenylate cyclase in striatal homogenates (Collier and Roy, 1974), monkey amygdalal homogenate (Walczak et al, 1979), and striatal slices (Minneman and Iversen, 1976); (b) opiate stimulated adenylate cyclase activity (Dismukes and Daly, 1975;Puri et al, 1975;Tang and Cotzias, 1978); and (c) opiate had no effect on the enzymatic activity (Bonnet, 1975;Tell et al, 1975; Katz and Catravas, 1977). It is only in the neuroblastoma x glioma hybrid NGlO8-15 cells that opiate attenuation of the intracellular cAMP level by inhibition of the enzyme adenylate cyclase has been demonstrated (Sharma et a]., 1975a(Sharma et a]., , 1977Traber et al, 1975;Brandt et a].…”
mentioning
confidence: 99%
“…However, stimulation of adenylate cyclase by opiates (Puri et al, 1975;Tang & Cotzias, 1978) and no effect on this enzymatic activity (Katz & Catravas, 1977) have also been reported. Ho et al (1973) found that prior administration of cyclic AMP to mice or rats antagonized morphine analgesia.…”
Section: Introductionmentioning
confidence: 99%